Benign peripheral nerve sheath tumor-varied clinical presentation - Kumar, Saravana; Kumar, Divya (International Surgery Journal, 2020)
Peripheral nerve sheath tumors (PNST) are a group of heterogeneous, often benign and a rare condition that originates from the neuroectodermal or neural crest and display features that mirror the elements of the nerve. Schwannomas are one such peripheral nerve sheath tumors which entirely are made up of benign neoplastic Schwann cells. The objective of this case report is to highlight the diverse clinical presentations of these swellings. In this presentation, reporting three cases of PNST in which two presented with neurological symptoms of paraesthesia and pain and one who was asymptomatic swelling over his neck. All of whom were diagnosed with an alternate soft tissue swelling post clinical examination and taken up for excision as there were no significant clinical evidence for imaging. Intra-operatively we noted that all were closely related to the peripheral nerve of that anatomical region. Histopathological study revealed it to be PNST. PNST and schwannoma in particular although an entity that is not so common to come across in the surgical clinic we need to have and high indices of suspicion when associated close to peripheral nerves and symptomatic of a nerve involvement as we discuss here below.